Study on the Changes of Liver and Kidney Function-Related Indicators and Clinical Significance in Patients with OSAHS - Rongyue Liu; Xiangdong Kong (Emergency Medicine International)
Purpose. To study the changes of liver and kidney function-related indexes in patients with obstructive sleep apnea hypopnea syndrome (OSAHS) and analyze their clinical significance. Method. Ninety OSAHS patients treated in our hospital from April 2019 to April 2021 were selected. According to the apnea-hypopnea Index (AHI), they were divided into mild OSAHS group (5 ≤ AHI < 15 times/h, 35 people), moderate OSAHS group (15 ≤ AHI < 30 times/h, 35 people), and severe OSAHS group (AHI ≥ 30 times/h, 20 people). In addition, 50 healthy people who underwent physical examination in our hospital at the same time were selected as the control group, and the liver and kidney function and polysomnography (PSG)-related indexes of the above subjects were detected, and the comparison between the groups was carried out. Result. The serum BUN and SCR levels of the severe group were significantly higher than those of the moderate group, the moderate group had significantly higher levels than the mild group, and the mild group had significantly higher levels than the control group (P<0.05). The blood AST level of the severe group was significantly lower than that of the moderate group, the moderate group had a significantly lower level than the mild group, and the mild group had a significantly lower level than the control group (P<0.05). The blood ALT level of the severe group was significantly higher than that of the moderate group, the moderate group had significantly a higher level than the mild group, and the mild group had a significantly higher level than the control group (P<0.05). The proportions of abnormal liver and kidney function in the control group, mild group, moderate group, and severe group were significantly different (P<0.05). The AHI of the severe group was significantly higher than that of the moderate group, the moderate group had a higher value than the mild group, and the mild group had a higher value than the control group (P<0.05). The ASpO2 and MSpO2 of the severe group were significantly lower than those of the moderate group, the moderate group had significantly lower values than the mild group, and the mild group had significantly lower values than the control group (P<0.05). Spearman correlation analysis showed that the liver and kidney function indexes of OSAHS patients were significantly correlated with PSG indexes (P<0.05). Conclusion. Patients with OSAHS will have obvious liver and kidney dysfunction, and the monitoring of liver and kidney function in such patients should be strengthened. If abnormality occurs, early intervention is recommended.